2020
DOI: 10.1186/s13317-020-00136-y
|View full text |Cite
|
Sign up to set email alerts
|

Autoantibodies directed against α1-adrenergic receptor and endothelin receptor A in patients with prostate cancer

Abstract: Background For prostate cancer, signaling pathways induced by over-boarding stimulation of G-protein coupled receptors (GPCR) such as the endothelin, α1- and β-adrenergic, muscarinic and angiotensin 1 receptors were accused to support the carcinogenesis. However, excessive receptor stimulation by physiological receptor ligands is minimized by a control system that induces receptor sensitization and down-regulation. This system is missing when so-called “functional autoantibodies” bind to the GP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This was a surprising unexpected effect. In healthy controls, which are included in many studies, these autoantibodies are only found in a small percentage [ 37 , 38 ]”.…”
Section: Resultsmentioning
confidence: 99%
“…This was a surprising unexpected effect. In healthy controls, which are included in many studies, these autoantibodies are only found in a small percentage [ 37 , 38 ]”.…”
Section: Resultsmentioning
confidence: 99%
“…While the autoantibody against the α 1D -AR appears antagonistic, several autoantibodies have been developed or discovered against the first or second extracellular loop of the α 1 -AR appear to be agonistic in behavior (Zhou et al, 2008;Karczewski et al, 2012;Hempel et al, 2016;Wallukat et al, 2020). While developing these autoantibodies for cardioprotective effects for the α 1A -AR may be tempting, they may not be regulated by the normal desensitization and negative feedback mechanisms common in GPCRs to turn off or wane the signal, resulting in abnormal and non-physiological signaling and proliferation (Zhou et al, 2008;Karczewski et al, 2018;Becker et al, 2019;Wallukat et al, 2020). This abnormal signaling and proliferation may account for the vascular damage that many autoantibodies also impart (Zhou et al, 2008;Karczewski et al, 2012Karczewski et al, , 2018Becker et al, 2019;Wallukat et al, 2020).…”
Section: Therapeutic Autoantibodies and Vaccines Against α 1 -Arsmentioning
confidence: 99%
“…While developing these autoantibodies for cardioprotective effects for the α 1A -AR may be tempting, they may not be regulated by the normal desensitization and negative feedback mechanisms common in GPCRs to turn off or wane the signal, resulting in abnormal and non-physiological signaling and proliferation (Zhou et al, 2008;Karczewski et al, 2018;Becker et al, 2019;Wallukat et al, 2020). This abnormal signaling and proliferation may account for the vascular damage that many autoantibodies also impart (Zhou et al, 2008;Karczewski et al, 2012Karczewski et al, , 2018Becker et al, 2019;Wallukat et al, 2020). Autoantibodies against the α 1 -AR have also been associated with coronary heart disease (Thyrian et al, 2018), cardiac remodeling and dysfunction (Zhou et al, 2005;, pre-eclampsia (Ma et al, 2013), thromboangiitis obliterans (Buerger's Disease) (Klein-Weigel et al, 2014), AD and vascular dementia (Karczewski et al, 2012(Karczewski et al, , 2018Hempel et al, 2016), and prostate cancer (Wallukat et al, 2020).…”
Section: Therapeutic Autoantibodies and Vaccines Against α 1 -Arsmentioning
confidence: 99%
See 1 more Smart Citation